2014
DOI: 10.1080/09712119.2014.963104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combining feed grade urea and a slow-release product on performance, dietary energetics and carcass characteristics of steers fed finishing diets

Abstract: Recent findings have shown that microbial nitrogen flow and digestible energy of diet are increased when urea (U) is combined with a slow-release urea product (SRU) in diets with a starch:acid detergent fibre (S:ADF) ratio of 4.5, while feed grade U has shown greater effects on growth performance or dietary energy utilization when the diet contains a S: ADF ratio of greater than 5.0. These results can be partially explained by the better synchronization of ruminal degradation rates between those U sources with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Those researchers argued that those results can be partially explained by the possible synchrony of ruminal degradation rates between urea and starch. At lower S:F ratios it is expected a lower positive effects, therefore, absence of improves of observed NE ratio over expected in urea treatment at 4:1 S:F ratio is not aberrant (observed-to-expected DMI = 0.98), as mentioned above, absence of improvements of observed NE ratio over expected (averaging 0.98) with conventional urea supplementation in diets with S:F ratios of 3, 4.5, and 5.5 was previously reported (López-Soto et al, 2015). The observed-to-expected dietary energy and intake are an important and practical application of current standards for energetics in nutrition research (Zinn et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Those researchers argued that those results can be partially explained by the possible synchrony of ruminal degradation rates between urea and starch. At lower S:F ratios it is expected a lower positive effects, therefore, absence of improves of observed NE ratio over expected in urea treatment at 4:1 S:F ratio is not aberrant (observed-to-expected DMI = 0.98), as mentioned above, absence of improvements of observed NE ratio over expected (averaging 0.98) with conventional urea supplementation in diets with S:F ratios of 3, 4.5, and 5.5 was previously reported (López-Soto et al, 2015). The observed-to-expected dietary energy and intake are an important and practical application of current standards for energetics in nutrition research (Zinn et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…It is important to consider that different responses of animals can be caused not only by different sources of urea supplementation but also by dietary variations (UIP level among others). However, in a growth-performance study conducted with feedlot steers, Lopez-Soto et al (2015) with a similar urea combination as in the present experiment in a diet with a S:F ratio of 4.5 observed a 6% of increases on NE of diet and decreases of 6% on the apparent retention per unit DM, while diets with conventional urea did not modify neither the observed-to-expected NE ratio nor the apparent retention per unit DMI, when was included in diets with a S:F ratios of 3, 4.5, and 5.5. It has been observed that in high-grain diets (ratio of starch vs ADF greater than 5 to 1) urea can be supplemented at 50% higher than that recommended with positive effects on growth performance and in dietary energy utilisation (Milton et al, 1997; Zinn et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have evaluated graded levels of SRU supplementation with inconsistent results on the performance of beef cattle [26,27,36]. The variation in the utilisation of urea levels may be due to several factors, such as the continuous availability of fermentable carbohydrate, level of RDP and nitrogenous compounds in the basal diet, feeding regiment-ad libitum or restricted feeding-and adaptation to urea feeding [37].…”
Section: Discussionmentioning
confidence: 99%